The Impact of Using “Revoring Exercise" to Learn Breaststroke for Female Students - Fadwa, R. M. S.; Ziyad, S. A.; Riadh, K.; Sabri, G. C.; Imen, A. (Advances in Social Sciences Research Journal, 2023)
This study aims to determine the effects of an educational program using "revoring exercise" on female students at Palestine Technical University/Ramallah Khadouri's branch learning to swim breaststroke. An experimental strategy was used. The sample contained (20) female students chosen intentionally, divided into two groups, one experimental and the other control, each with (10) students. The population was made up of (28) female third- and fourth-year physical education college students. The final breaststroke performance evaluation form and the teaching program based on the Revoring Exercise were employed as research materials.The instructional program was implemented over the course of (8) weeks and consisted of (3) teaching units, each lasting (90) minutes. Data analysis was performed using SPSS. The experimental group members' skill performance in breaststroke swimming improved as a result of the educational program employing revoring exercise, which produced learning abilities in breaststroke skills, according to the results. Based on the findings, the researchers advise using reviewing exercises to teach students how to move while studying other forms of swimming for other sports during practical lessons in physical education colleges.